Mean platelet volume: An economical diagnostic marker of cardiovascular risk assessment in altered fasting blood glucose levels - Kapoor, Shivali; Kaur, Manjit; Rana, Amrit Pal Singh; Suryanarayan, A (Asian Journal of Medical Sciences, 2015)
Background: Platelets with altered morphology or large size are more thrombogenic and are likely to be associated with increased risk of vascular disease. Platelet parameters especially high mean platelet volume (MPV) has been reported in diabetic patients as major contributing factor. The aim of the present study was to find correlation between fasting blood glucose value and hematological variables (PC and MPV), not only in diabetics, but also in the normoglycemic subjects and patients with impaired fasting blood glucose levels. Materials and Methods: In the present study 3471 subjects were analyzed retrospectively and categorized into three groups based on the fasting blood glucose levels as Group I - normoglycemics (FBG ? 109 mg/dl, n = 1158), Group II- impaired fasting blood glucose (FBG ? 126 mg/dl, n = 1158) and Group III – Diabetics (FBG ? 127 mg/dl, n = 1155). Results: We found progressive increase in value of MPV with the increasing FBG levels, in the following order: G1 (8.44 ± 0.842 fl), G2 (8.98 ± 0.898 fl), G3 (9.31 ± 0.967 fl). The platelet count however, did not show much statistical significance with rising glucose levels. Conclusions: MPV increased proportionally with increasing plasma glucose levels. Although the variation between the normoglycemics and impaired fasting group was not very significant, the parameters still showed progressive increase with rising sugar levels significant in diabetic group. Asian Journal of Medical Sciences Vol.7(1) 2015 30-33